Penerapan Metode Profile Matching untuk Keputusan Siswa Penerima Beasiswa Berbasis Web: Studi Kasus: SMPN 2 Wewewa Tengah - Artoce Rison Ngongo; Andreas Ariyanto Rangga; Felysitas Ema O Sanga (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2024)
The very rapid development of information technology over time has felt the benefits of most people in the fields of education, health, entertainment, information sources, the world of business and communication without limitations of place and time. The internet is one of the latest communication information technologies, the internet has almost unlimited reach and reaches almost all groups in Indonesian society. Information technology is a technology that is developing rapidly at present. The real proof of current technological developments is computers. Computers are designed to automatically receive and store data (Input), process and produce data (output) using programs stored in computer memory. The use of Information Technology is not only limited to companies or government agencies but can also be used in the world of education. Research results System results can collect alternative student assessment data as well as criteria and sub-criteria data. The system can make decisions by calculating the core factor and secondary factor values ​​for each alternative and sub-criteria so that the student's decision can be accepted.